PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DESA DI KABUPATEN BANDUNG - Agustina Setiawan; Utang Suwaryo; Mudiyati Rahmatunnisa (Jurnal Academia Praja, 2020)
This research is intended to study community participation in village development planning in Bandung regency, West Java Province. The question raised is related to community participation in Sayati village, Margahayu sub-district; Nanjung Village, Margaasih District; Margamukti Village, Pangalengan District; and Ciburial Village, Cimenyan District, Bandung Regency, West Java Province. Participation is intended more to explore the process of involvement in expressing opinions, opportunities in expressing opinions and opportunities in implementing policy planning and development programs in the four selected villages. In this study, researchers used the Arnstein ladder model developed by Hart as the grand analysis theory in this study. In this study used a qualitative method so that the main instrument is the researcher himself. The technique used in this study is observation which is completed with in-depth interviews conducted with key informants and making field notes about events that researchers encounter in the field. The results showed that, community participation in village development planning in accordance with formal procedures for the formulation of development planning in Bandung Regency, community participation in village development planning which only took the form of physical presence and community participation in village development planning which only took the form of participation ideas and ideas alone by ignoring participation in physical presence.